Meta-form near eye visor - Hong, Chuchuan (My University, 2017)
This thesis is about meta-form near-eye visor (NEV). Near eye visor is the core component in a head mounted display (HMD), because it directly decides the quality and volume of HMD. Regarding freeform NEV, a limitation on Field of View (FOV) is proposed. A flat shape phase mask visor, termed here as meta-form visor, is used to replace the freeform NEV to lift the limitation. Metasurface is chosen to work as the visor, because of its flat surface and capability to implement spatial modulation to incident light wave. Metasurface is a two-dimensional array of subwavelength scatterers. Meta-form visor’s vision performance is simulated in Zemax. Image simulation using the designed metasurface is performed in Lumerical FDTD. In this design dielectric material is chosen to compose the metasurface, for its lower loss in visible frequency than metallic metasurface.
Thesis (Master's)--University of Washington, 2017-06
Keywords: metasurface; near eye display; Electrical engineering; Electrical engineering